Carbon dioxide absorbing material, carbon dioxide absorbing device, and carbon dioxide absorbing method

By using carbon dioxide absorption materials that combine potassium ferrite powder with resin, the problems of slow absorption speed and reduced reuse speed of existing sodium ferrite materials are solved, and efficient carbon dioxide absorption effect is achieved.

CN119816366APending Publication Date: 2025-04-11FUJIFILM CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380062662.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-07-11
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing sodium ferrite material absorbs carbon dioxide at a slower rate during initial use, and the absorption rate during re-use is greatly reduced.

Method used

Potassium ferrite powder is used as the carbon dioxide absorption material and a granular material is formed by combining resin. The absorption rate is faster when used initially and the absorption rate is reduced less when used again.

Benefits of technology

It achieves a fast carbon dioxide absorption rate during initial use, a less reduction in absorption rate during reuse, and has good carbon dioxide absorption capacity at room temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005289563790000011
    Figure HDA0005289563790000011
  • Figure HDA0005289563790000012
    Figure HDA0005289563790000012
  • Figure HDA0005289563790000021
    Figure HDA0005289563790000021
Patent Text Reader

Abstract

The present invention provides a carbon dioxide absorbing material comprising potassium ferrite powder, a carbon dioxide absorbing device comprising the carbon dioxide absorbing material, and a carbon dioxide absorbing method comprising a step of bringing the carbon dioxide absorbing material into contact with a carbon dioxide-containing gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbon dioxide absorbing material, a carbon dioxide absorbing device and a carbon dioxide absorbing method. Background Art

[0002] In recent years, efforts have been made around the world to realize a decarbonized society. Under such circumstances, research and development of carbon dioxide absorbing materials are being conducted to recover carbon dioxide in exhaust gases discharged from power plants, factories, etc. (for example, Patent Document 1). In addition, research is also being conducted on DAC (Direct Air Capture) technology that directly recovers carbon dioxide from the atmosphere.

[0003] Previous technical literature

[0004] Patent Literature

[0005] Patent document 1: WO2021 / 117623A1 Summary of the invention

[0006] Technical issues to be solved by the invention

[0007] Patent Document 1 discloses that sodium ferrite absorbs carbon dioxide. Patent Document 1 also discloses that after absorbing carbon dioxide (i.e., after initial use), sodium ferrite is heated to remove carbon dioxide from the sodium ferrite, and then used to absorb carbon dioxide again, i.e., reused as a carbon dioxide absorbing material (for the above, refer to the embodiment of Patent Document 1). However, the inventors' research has revealed that when sodium ferrite is used as a carbon dioxide absorbing material, the absorption rate of carbon dioxide during initial use is relatively slow; and the absorption rate of carbon dioxide during reuse is significantly lower than the absorption rate during initial use.

[0008] Means for solving technical problems

[0009] An object of one aspect of the present invention is to provide a carbon dioxide absorber having a high carbon dioxide absorption rate when initially used and a small decrease in the absorption rate when reused.

[0010] As a result of repeated intensive studies, the present inventors have newly discovered that potassium ferrite powder has carbon dioxide absorption capacity, that the carbon dioxide absorption rate is fast when initially used, and that the decrease in the absorption rate is small when used again.

[0011] That is, one embodiment of the present invention is as follows.

[0012] [1] A carbon dioxide absorbent comprising potassium ferrite powder.

[0013] [2] The carbon dioxide absorbent according to [1], further comprising a resin.

[0014] [3] The carbon dioxide absorbent according to [2], which is in a granular form.

[0015] [4] A carbon dioxide absorption device comprising the carbon dioxide absorption material according to any one of [1] to [3].

[0016] [5] The carbon dioxide absorption device according to [4], further comprising:

[0017] The heating unit heats the carbon dioxide absorbing material.

[0018] [6] A method for absorbing carbon dioxide, comprising the following steps:

[0019] The carbon dioxide absorbing material described in any one of [1] to [3] is brought into contact with a carbon dioxide-containing gas.

[0020] [7] The carbon dioxide absorption method according to [6] further comprises the following steps:

[0021] Desorbing at least a portion of the carbon dioxide absorbed by the carbon dioxide absorbing material by heating the carbon dioxide absorbing material after contact with the carbon dioxide-containing gas; and

[0022] The heated carbon dioxide absorbing material is brought into contact with a gas containing carbon dioxide.

[0023] Effects of the Invention

[0024] According to one aspect of the present invention, a carbon dioxide absorbing material can be provided, which has a faster carbon dioxide absorption rate when initially used and a smaller decrease in absorption rate when reused. In addition, according to one aspect of the present invention, a carbon dioxide absorbing device including the carbon dioxide absorbing material and a carbon dioxide absorbing method using the carbon dioxide absorbing material can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 ] The X-ray diffraction spectra obtained for Example 1 and Example 2 are shown together with the reference pattern.

[0026] Figure 2 This is a graph showing the carbon dioxide absorption rate of Example 1, Example 2, Comparative Example 1, and Comparative Example 2 at the time of initial use.

[0027] Figure 3 This is a graph showing the carbon dioxide absorption rate when Example 1, Example 2, Comparative Example 1, and Comparative Example 2 are reused.

[0028] Figure 4 This is a graph showing the carbon dioxide absorption rate at the time of initial use and at the time of repeated use of Example 3. DETAILED DESCRIPTION

[0029] [Carbon dioxide absorber]

[0030] One aspect of the present invention relates to a carbon dioxide absorbent including potassium ferrite powder. The carbon dioxide absorbent will be described in further detail below.

[0031] <Potassium ferrite powder>

[0032] The carbon dioxide absorbent material contains potassium ferrite powder.

[0033] In the present invention and this specification, "powder" refers to an aggregate of a plurality of particles. The term "aggregate" is not limited to a state where particles constituting the aggregate are in direct contact, but also includes a state where a resin or the like described below is interposed between particles.

[0034] In the present invention and this specification, "potassium ferrite powder" refers to a powder in which the alkali metal atoms that account for the largest proportion on an atomic % basis among the alkali metal atoms contained in the powder are potassium atoms, and the crystal structure of potassium ferrite is detected as the main phase by X-ray diffraction analysis. The main phase refers to the structure to which the diffraction peak with the highest intensity in the X-ray diffraction spectrum obtained by X-ray diffraction analysis belongs. In the case where the diffraction peak with the highest intensity in the X-ray diffraction spectrum obtained by X-ray diffraction analysis belongs to the crystal structure of potassium ferrite, it is judged that the crystal structure of potassium ferrite is detected as the main phase. In the case where only a single crystal structure is detected by X-ray diffraction analysis, the detected crystal structure is set as the main phase. Regarding potassium ferrite powder, in one embodiment, the crystal structure may be a single phase, and in another embodiment, it may also include multiple crystal structures. The case where "the crystal structure is a single phase" refers to the case where only one diffraction pattern showing a specific crystal structure is observed in the X-ray diffraction analysis. In contrast, when multiple crystal structures are included, in the X-ray diffraction analysis, two or more diffraction patterns representing specific crystal structures are observed. In the attribution of the diffraction pattern, for example, the database of the International Centre for Diffraction Data (ICDD), the Inorganic Crystal Structure Database (ICSD), etc. can be referenced. Regarding the diffraction pattern of potassium ferrite, for example, the "ICSD collection code (collection code): 157785" of the Inorganic Crystal Database (ICSD) can be referenced.

[0035] Potassium ferrite is a type of ferrite base. Among ferrite bases, when the atoms constituting the crystal structure are alkali metal atoms, iron atoms and oxygen atoms, it has a composition represented by the composition formula: AFeO2. In the above composition formula, "A" represents an alkali metal atom. In potassium ferrite powder, the alkali metal atom that accounts for the largest proportion of the alkali metal atoms contained in the powder on an atomic % basis is a potassium atom, and the alkali metal atoms contained in the powder may also be only potassium atoms.

[0036] As a result of repeated and in-depth studies, the inventors have found that potassium ferrite powder, for example, has a faster carbon dioxide absorption rate during initial use and a smaller decrease in absorption rate during repeated use than sodium ferrite powder, which is a type of ferric acid base. In addition, potassium ferrite powder is known to be able to exhibit carbon dioxide absorption capacity at temperatures around room temperature (e.g., around 20°C to 30°C), and therefore has excellent versatility.

[0037] Furthermore, according to the research of the present inventors, potassium carbonate, which is a kind of potassium salt, has the ability to absorb carbon dioxide, but the desorption temperature obtained by the method described in the first column of the examples described later is as high as 220° C. to 230° C. In contrast, the desorption temperature of potassium ferrite powder is lower than that of potassium carbonate, so the absorbed carbon dioxide can be desorbed by heating to a temperature of 200° C. or less, for example, and it is also found that the absorption rate of carbon dioxide is faster when it is used initially and when it is used again than potassium carbonate.

[0038] Since the potassium ferrite powder is included, the carbon dioxide absorbing material can be a carbon dioxide absorbing material that absorbs carbon dioxide faster when initially used and has a smaller decrease in absorption rate when reused. In addition, the carbon dioxide absorbing material can exert its carbon dioxide absorption capacity at a temperature around room temperature, and further, for example, by heating to a temperature below 200° C., the absorbed carbon dioxide can be released. The carbon dioxide absorbing material can be used in a humidity environment of about 40% to 50% relative humidity, for example. However, the humidity environment is illustrative, and the carbon dioxide absorbing material is not limited to use in this humidity environment.

[0039] (Method for producing potassium ferrite powder)

[0040] The method for producing the potassium ferrite powder contained in the above-mentioned carbon dioxide absorbing material is not particularly limited. The potassium ferrite powder contained in the above-mentioned carbon dioxide absorbing material can be produced by any production method. Hereinafter, as an example of a method for producing potassium ferrite powder, a solid phase method is described. The solid phase method is a method for producing potassium ferrite powder by calcining a mixture obtained by mixing a plurality of solid raw materials.

[0041] As solid raw materials used in the solid phase method, one or more compounds of potassium atoms and one or more compounds of iron atoms can be cited. These compounds can be oxides, hydroxides, etc. As a compound of potassium atoms, potassium hydroxide is preferred from the viewpoint that the temperature during calcination described later can be set to a lower temperature than when other potassium atom compounds are used. In the case of obtaining a powder of potassium ferrite having a composition represented by the composition formula: KFeO2, the mixing ratio of the compound of potassium atoms and the compound of iron atoms can be set to a mixing ratio in which the molar ratio of K atoms to Fe atoms is about 1:1. Regarding the mixing of solid raw materials, it can be carried out under any conditions by a known mechanism that can crush and mix the raw material mixture, such as a mortar and pestle, a grinder (cutter, ball mill, bead mill, roller mill, jet mill, hammer mill, grinder, etc.). In addition, the mixing of solid raw materials is not limited to being carried out under dry conditions. It can also be mixed under wet conditions, such as adding a solvent such as water, and mixing in a slurry state. The above mixing can be carried out, for example, in an atmosphere at room temperature (e.g., about 20°C to 30°C).

[0042] After the above mixing, the obtained raw material mixture can be calcined. During the calcination, the raw material mixture can be crystallized, thereby forming a crystal structure of potassium ferrite. As calcination conditions, for example, the calcination temperature can be set in the range of 400°C to 800°C. The calcination temperature can be, for example, the atmosphere temperature in the device for calcination (for example, the furnace temperature of a heating furnace). The calcination time can be set in the range of 3 hours to 10 hours. However, the above range is for illustration, as long as the calcination is carried out under the conditions that the crystal structure of potassium ferrite can be formed. Calcination can be carried out, for example, in an atmospheric atmosphere.

[0043] The calcined product after the calcination can be arbitrarily subjected to a dry or wet pulverization step. The pulverization can be carried out under any conditions by a known mechanism such as a mortar and pestle, a pulverizer (cutter, ball mill, bead mill, roller mill, jet mill, hammer mill, attritor, etc.).

[0044] Regarding the content of potassium ferrite powder in the above-mentioned carbon dioxide absorbent, with the total mass of the carbon dioxide absorbent being 100 mass%, it can be, for example, 50 mass% or more, 60 mass% or more, or 70 mass% or more, and can be 100 mass%, or less than 100 mass%, less than 100 mass%, or less than 90 mass%.

[0045] <Resin>

[0046] The carbon dioxide absorbent material may contain only potassium ferrite powder, or may contain one or more other components in addition to potassium ferrite powder. As the other component, for example, resin can be cited. The resin can play the role of a binder in the carbon dioxide absorbent. In the present invention and this specification, "resin" includes homopolymers and copolymers. The resin may be a thermoplastic resin or a thermosetting resin, and as an example of a resin, a polypropylene resin can be cited. In the case where the carbon dioxide absorbent material contains a resin, the content of the resin, with the total mass of the carbon dioxide absorbent being 100 mass%, for example, may be less than 50 mass%, less than 40 mass%, or less than 30 mass%, and may be more than 5 mass%, more than 10 mass%, or more than 20 mass%. In the case where the carbon dioxide absorbent material contains a resin, the resin may contain only one type, or may contain two or more types in any mixing ratio. In the case where two or more resins are contained, the content of the resin is the total content of the two or more resins.

[0047] The carbon dioxide absorbing material containing resin can be, for example, a resin composition (i.e., a kneaded product) obtained by kneading potassium ferrite powder and resin, which can be cut into particles of any shape. The particles can be in any shape such as granular, flaky, or columnar. The granular carbon dioxide absorbing material can be obtained by cutting the kneaded product containing potassium ferrite powder and resin into any shape using a commercially available granulator or a granulator of a known structure.

[0048] [Carbon dioxide absorption device]

[0049] One aspect of the present invention relates to a carbon dioxide absorption device including the above-mentioned carbon dioxide absorption material.

[0050] For example, the carbon dioxide absorption device may include a carbon dioxide absorption section that contains the carbon dioxide absorption material. The carbon dioxide-containing gas is allowed to ventilate the carbon dioxide-containing gas to the carbon dioxide absorption section so that the carbon dioxide-containing gas comes into contact with the carbon dioxide absorption material, and the carbon dioxide absorption material may absorb a portion or all of the carbon dioxide (i.e., carbon dioxide) contained in the carbon dioxide-containing gas. Then, by recovering the gas ventilated to the carbon dioxide absorption section, a gas having a lower carbon dioxide concentration than before venting may be obtained. The structure of the carbon dioxide absorption section is not limited, and known techniques related to carbon dioxide absorption devices may be applied.

[0051] In one embodiment, the carbon dioxide absorption device may include a heating unit for heating the carbon dioxide absorption device. For example, a part or all of the carbon dioxide absorbed by the carbon dioxide absorption material can be desorbed by heating the carbon dioxide absorption material in contact with the carbon dioxide-containing gas. After the desorption, the carbon dioxide absorption material can be made to absorb carbon dioxide by making the carbon dioxide absorption material contact with the carbon dioxide-containing gas. The structure of the heating unit is not limited, and known techniques related to carbon dioxide absorption devices can be applied. The heating unit can, for example, heat the carbon dioxide absorption material in the carbon dioxide absorption unit to a temperature of 100°C or more and 200°C or less. The heating time is not particularly limited, as long as it is set to a time that allows a part or all of the carbon dioxide absorbed by the carbon dioxide absorption material to be desorbed. For example, the carbon dioxide desorbed from the carbon dioxide absorption material can be recovered by a known method and stored underground, or it can also be applied to uses that can utilize carbon dioxide.

[0052] [Carbon dioxide absorption method]

[0053] One aspect of the present invention relates to a method for absorbing carbon dioxide, comprising the step of bringing the carbon dioxide absorbing material into contact with a gas containing carbon dioxide.

[0054] Furthermore, the carbon dioxide absorption method may further include the steps of: heating the carbon dioxide absorption material after contact with the carbon dioxide-containing gas to release at least a portion of the carbon dioxide absorbed by the carbon dioxide absorption material; and contacting the heated carbon dioxide absorption material with the carbon dioxide-containing gas.

[0055] For example, the carbon dioxide absorption device can be used to implement the carbon dioxide absorption method. For details of the carbon dioxide absorption method, reference can be made to the above description related to the carbon dioxide absorption device.

[0056] Regarding the carbon dioxide absorption device and the carbon dioxide absorption method, the carbon dioxide-containing gas may be, for example, waste gas discharged from a power plant, a factory, etc. The carbon dioxide absorption device and the carbon dioxide absorption method may be used to separate and recover carbon dioxide from the waste gas. Furthermore, the carbon dioxide absorption device and the carbon dioxide absorption method may also be used for DAC that directly recovers carbon dioxide from the atmosphere. That is, in one embodiment, the carbon dioxide-containing gas may be the atmosphere.

[0057] Example

[0058] Hereinafter, the present invention will be described based on examples. However, the present invention is not limited to the embodiments shown in the examples. Unless otherwise specified, the processes and evaluations described below are carried out in an atmospheric atmosphere. Furthermore, unless otherwise specified, the processes and evaluations described below are carried out at an atmospheric temperature of 23°C ± 1°C.

[0059] [Example 1]

[0060] Potassium hydroxide [KOH] and α-iron (III) oxide [α-Fe2O3] were weighed so that the molar ratio of potassium atoms to iron atoms became 1:1 and put into a crusher (Wonder Crusher WC-3 manufactured by OSAKA CHEMICAL Co., Ltd.), and the variable speed turntable of the crusher was set to "3" and crushing and mixing treatment was carried out for 60 seconds to obtain a powder of the raw material mixture (hereinafter referred to as "mixed powder").

[0061] Next, the obtained mixed powder was calcined in a heating furnace at a furnace temperature of 400° C. (hereinafter referred to as “calcination temperature”) for 8 hours, and then pulverized for 60 seconds using a pulverizer (Wonder Crusher WC-3 manufactured by OSAKA CHEMICAL Co., Ltd.), with the variable speed turntable of the pulverizer set to “3”, to obtain potassium ferrite powder.

[0062] The potassium ferrite powder obtained in this manner was used as the carbon dioxide absorber of Example 1 and was subjected to various evaluations described below.

[0063] [Example 2]

[0064] Potassium ferrite powder was obtained by the method described in Example 1 except that the calcination temperature was changed to 600°C.

[0065] The potassium ferrite powder obtained in this manner was used as the carbon dioxide absorber of Example 2 and was subjected to various evaluations described below.

[0066] [Comparative Example 1]

[0067] Sodium hydroxide [NaOH] and α-iron (III) oxide [α-Fe2O3] were weighed so that the molar ratio of sodium atoms to iron atoms was 1:1 and put into a crusher (Wonder Crusher WC-3 manufactured by OSAKA CHEMICAL Co., Ltd.), and the variable speed dial of the crusher was set to "3" and crushing and mixing treatment was carried out for 60 seconds to obtain a mixed powder.

[0068] Next, the obtained mixed powder was calcined at a calcination temperature of 600° C. for 8 hours and then pulverized for 60 seconds using a pulverizer (Wonder Crusher WC-3 manufactured by OSAKA CHEMICAL Co., Ltd.) with the variable speed dial of the pulverizer set to “3” to obtain sodium ferrite powder.

[0069] The sodium ferrite powder obtained in this manner was used as the carbon dioxide absorbent of Comparative Example 1 and was subjected to various evaluations described below.

[0070] [Comparative Example 2]

[0071] As the carbon dioxide absorbent of Comparative Example 2, commercially available potassium carbonate powder (Wako 1st Grade potassium carbonate manufactured by FUJIFILM Wako Pure Chemical Corporation) was added to the various evaluations described below.

[0072] [Example 3]

[0073] The potassium ferrite powder obtained by the method described in Example 1 and a polypropylene resin (MA3H manufactured by Nippon Polypropylene Co., Ltd.) were kneaded using a biaxial kneader (potassium ferrite powder content: 70 mass %, polypropylene resin content: 30 mass %), and pellets were obtained using a pelletizer.

[0074] The pellets obtained in this manner were used as the carbon dioxide absorber of Example 3 and were subjected to various evaluations described below.

[0075] [Evaluation method]

[0076] <Confirmation of crystal structure>

[0077] The crystal structure of each carbon dioxide absorbent (powder) of Example 1, Example 2 and Comparative Example 1 was confirmed by X-ray diffraction analysis (XRD). As a measuring device, X'Pert Pro of PANalytical, which is a powder X-ray diffraction device, was used. The measuring conditions are shown below.

[0078] -Measurement conditions-

[0079] X-ray source: CuKα rays

[0080] 〔wavelength: (0.154nm, output: 40mA, 45kV)

[0081] Scanning range: 20°<2θ<70°

[0082] Scanning interval: 0.05°

[0083] Scanning speed: 0.33° / min

[0084] The results of the X-ray diffraction analysis confirmed that the carbon dioxide absorbents (powders) of Examples 1 and 2 were potassium ferrite powders, and the carbon dioxide absorbent (powder) of Comparative Example 1 was sodium ferrite powder. In addition, it was confirmed that the crystal structure of each of the carbon dioxide absorbents of Examples 1, 2, and Comparative Example 1 was a single phase. Figure 1 ] The X-ray diffraction spectra obtained for Example 1 and Example 2 are shown together with the reference pattern. Figure 1 The reference pattern shown is a line pattern of "ICSD collection code: 157785" published in the Inorganic Crystal Database (ICSD).

[0085] <Performance evaluation of carbon dioxide absorbent>

[0086] (1) Measurement of carbon dioxide absorption rate during initial use

[0087] A carbon dioxide concentration meter (GCH-2018 manufactured by MOTHERTOOL CO., LTD.) and a carbon dioxide absorber (5 g of powder for Examples 1 to 3, Comparative Examples 1 and 2, and 8 g of pellets for Example 3) were placed in a 1.5L desiccator, and the carbon dioxide concentration inside the desiccator was adjusted to about 5000 ppm (parts per million) on a volume basis. The carbon dioxide concentration inside the desiccator was observed to decrease over time for 2 hours. The temperature and humidity inside the desiccator at this time were 25°C and the relative humidity was 50%.

[0088] Regarding Example 1 and Example 2, the change over time of the carbon dioxide concentration inside the dryer until 30 minutes (min) from the start of observation (i.e., the absorption rate, the same below) is shown in Table 2 and Figure 2 .

[0089] Regarding Comparative Examples 1 and 2, the changes over time in the carbon dioxide concentration inside the dryer until 60 minutes have passed from the start of observation are shown in Tables 2 and 3. Figure 2 .

[0090] Regarding Example 3, the change in carbon dioxide concentration in the dryer over time until 60 minutes have passed is shown in Tables 4 and Figure 4 .

[0091] (2) Determination of the separation temperature

[0092] After observing the above (1) for 2 hours, the interior of the desiccator was filled with carbon dioxide and left for 12 hours, thereby allowing each carbon dioxide absorbent to saturate with carbon dioxide.

[0093] A portion of the carbon dioxide absorbing material saturated with carbon dioxide was collected, and the peak temperature of the weight loss was measured using a thermogravimetric differential thermal analyzer (TG (Thermogravimeter: thermogravimetric analyzer) / DTA (Differential Thermal Analyzer: differential thermal analyzer)), and the peak temperature was set as the desorption temperature of carbon dioxide. The desorption temperature obtained for each carbon dioxide absorbing material is shown in Table 1. Each carbon dioxide absorbing material was heated to near the desorption temperature obtained by the above method, so that the absorbed carbon dioxide could be desorbed from the carbon dioxide absorbing material.

[0094] (3) Measurement of carbon dioxide absorption rate during reuse

[0095] In the above (2), a portion of the carbon dioxide absorbing material saturated with carbon dioxide was collected and heated in an oven at an internal temperature of 150° C. for 3 hours.

[0096] The carbon dioxide absorption rate of the heated carbon dioxide absorbent was measured by the method described in (1) above.

[0097] Regarding Examples 1 and 2, the changes over time in the carbon dioxide concentration inside the dryer until 30 minutes have passed from the start of observation are shown in Tables 3 and 4. Figure 3 .

[0098] Regarding Comparative Examples 1 and 2, the changes over time in the carbon dioxide concentration inside the dryer until 60 minutes after the start of observation are shown in Tables 3 and 4. Figure 3 .

[0099] As shown in Table 3 and Figure 3 As shown in Table 1, the carbon dioxide absorbing material (potassium carbonate powder) of Comparative Example 2 did not show carbon dioxide absorption capacity when reused. This is considered to be because, as shown in Table 1, the desorption temperature was 220°C and was significantly higher than the heating temperature (150°C) in the above oven, so the saturated carbon dioxide was not desorbed during the heating in the above oven.

[0100] Regarding Example 3, the change in carbon dioxide concentration in the dryer over time until 60 minutes have passed is shown in Tables 4 and Figure 4 .

[0101] [Table 1]

[0102] Table 1: Detachment temperature

[0103] Example 1 Example 2 Comparative Example 1 Comparative Example 2 Example 3 Detachment temperature(℃) 156 160 120 220 156

[0104] [Table 2]

[0105] Table 2: Absorption rate during initial use

[0106] Time (minutes) Example 1 Example 2 Comparative Example 1 Comparative Example 2 0 5055 5024 5114 5219 1 3850 3844 4500 5000 3 2655 2711 3366 4651 5 1599 1401 2555 4057 10 514 612 1525 3140 20 81 71 489 2140 30 8 5 215 1458 60 18 607

[0107] [Table 3]

[0108] Table 3: Absorption rate when used again

[0109] Time (minutes) Example 1 Example 2 Comparative Example 1 Comparative Example 2 0 5066 5003 5222 5174 1 3799 3711 5006 5174 3 2554 2806 4711 5174 5 1506 1334 4011 5176 10 501 509 3099 5177 20 83 60 2201 5123 30 5 3 1511 5122 60 599 5127

[0110] [Table 4]

[0111] Table 4: Absorption rate during initial use and absorption rate during repeated use of Example 3

[0112] Time (minutes) Example 3_ Initial use Example 3: When using again 0 5222 5155 1 5006 4988 3 4711 4809 5 4011 3988 10 3099 3047 20 2201 2111 30 1511 1478 60 599 567

[0113] As shown in Table 1, the carbon dioxide absorbents of Examples 1 to 3 have lower desorption temperatures than the carbon dioxide absorbent of Comparative Example 2 (potassium carbonate).

[0114] From Table 2 and Figure 2 The results shown in Table 3 and Table 4 show that the carbon dioxide absorption rate of the carbon dioxide absorption materials of Examples 1 and 2 is faster than that of the carbon dioxide absorption materials of Comparative Examples 1 and 2 in the initial use. Figure 3 The results shown in Table 3 and Table 4 show that the carbon dioxide absorption materials of Examples 1 and 2 show the same carbon dioxide absorption rate when reused as when initially used. Figure 3 As shown, the carbon dioxide absorption rate of the carbon dioxide absorbent (sodium ferrite powder) of Comparative Example 1 is significantly lowered when it is reused compared to when it is initially used.

[0115] From Table 4 and Figure 4 The results show that even when potassium ferrite powder is mixed with a resin and used as pellets, it can be confirmed that the carbon dioxide absorption rate is faster at the initial use, and the carbon dioxide absorption rate is comparable to that at the initial use when used again.

[0116] Industrial Applicability

[0117] One embodiment of the present invention is useful in various technical fields where reduction of carbon dioxide emissions is desired.

Claims

1. A carbon dioxide absorbing material comprising potassium ferrite powder. 2 . The carbon dioxide absorbing material according to claim 1 , further comprising a resin. The carbon dioxide absorbing material according to claim 2 , which is in a granular form. 4 . A carbon dioxide absorption device comprising the carbon dioxide absorption material according to claim 1 .

5. The carbon dioxide absorption device according to claim 4, further comprising: The heating unit heats the carbon dioxide absorbing material.

6. A method for absorbing carbon dioxide, comprising the following steps: The carbon dioxide absorbing material according to any one of claims 1 to 3 is brought into contact with a gas containing carbon dioxide.

7. The carbon dioxide absorption method according to claim 6, further comprising the following steps: Desorbing at least a portion of the carbon dioxide absorbed by the carbon dioxide absorbing material by heating the carbon dioxide absorbing material after contact with the carbon dioxide-containing gas; and The heated carbon dioxide absorbing material is contacted with a carbon dioxide-containing gas.

Citation Information

Patent Citations

  • Sodium ferrite particle powder and production method thereof

    WO2021117623A1